Method for determining the chirality sign of peptide nanotubes using the dipole moments vectors calculations - Bystrov, Vladimir (2021)
In this work the method for calculating the index and sign of chirality using the values of the dipole moments of each individual dipeptides forming a helix structure of a peptide nanotube is proposed. Calculations of the individual dipeptide dipole moments using semi-empirical quantum method PM3 and force field method Amber are preformed in the frame of HyperChem software package. Results obtained for diphenylalnine (FF) peptide nanotube (PNT) with two different initial chirality L-FF and D-FF shows correct results of the chirality changes on D and L for helical PNT, corresponding to the law of the change in the sign of chirality, when the hierarchical structure of the molecular system becomes more complex. The results obtained give us a new opportunity to see the physical basis for the formation of the type and sign of chirality and open up new possibilities for a quantitative study of this phenomenon. This approach can be applied to other similar structures and peptide nanotubes based on other amino acids and dipeptides.